PELANGGARAN ATAS KEWAJIBAN NOTARIS DIKAITKAN DENGAN KETIDAKHADIRAN NOTARIS DALAM PENANDATANGANAN AKTA PERJANJIAN KREDIT BANK - IIN HERDITA SIRAIT (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Saidin3. Rudy Haposan Credit/Loan agreement is one of the agreements made between bank as the creditor and consumers as the debtor. The authority of a notary in the issuance of a bank loan agreement deed is grounded on these provisions. The liability of a notary who performs an illegal act in the issuance of a bank loan agreement deed is that the notary is obliged to civilly take the responsibility which is to pay the compensation to the financially harmed parties in accordance with the provision in Article 1365 of the Civil Code and Article 84 of UUJN No. 30/2004 in conjunction with UUJN No. 2/2014. The legal consequence of signing an authentic loan agreement deed in which the notary is absent is the authentic deed is degraded to be an underhanded deed which no longer has the complete proving force for all parties in case a dispute takes place at the court in the future time.Keywords: Violation of Liability, Notary and Loan Agreement Deed